Effect of the green tea on the formation of the bacterian plaque for Streptococcus mutans. - Moromi Nakata, Hilda (2006)
In order to determine the effect of the infusion of the green tea to 10 % w/v in plaque formation for Streptococcus mutans ATCC 25175; carried out successive cultures every 24 hours, up to 7 days, in broth saccharose to 5 %. The results showed a notarial decrease and lack of adherence in the plaque formation at wiere of nichrone cultures with infusion of green tea with respect at control culture.